2004
DOI: 10.1385/endo:25:3:229
|View full text |Cite
|
Sign up to set email alerts
|

Klotho Protein Activates the PKC Pathway in the Kidney and Testis and Suppresses 25-Hydroxyvitamin D<SUB>3</SUB> 1α-Hydroxylase Gene Expression

Abstract: Homozygous Klotho mutant (kl-/-) mice exhibit a variety of phenotypes resembling human aging, including arteriosclerosis, infertility, skin atrophy, osteoporosis, and short life span. Calcium abnormality, one of the phenotypes in kl-/- mice, is thought to be due to the elevated gene expression of 25-hydroxyvitamin D3 1alpha-hydroxylase in the kidney. We studied 25-hydroxy-vitamin D3 1alpha-hydroxylase gene expression using a Klotho plasmid that we had previously constructed for Klotho protein production. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 24 publications
1
27
0
1
Order By: Relevance
“…41 Soluble Klotho has been reported to act directly on the proximal tubules to increase phosphate excretion independent of Fgf23. 16 Moreover, Imai et al 42 reported that soluble Klotho suppresses Cyp27b1 through a pathway independent of cyclic adenosine monophosphate (cAMP) and protein kinase C (PKC). However, no measureable differences in serum soluble Klotho between knockout and wild-type mice were observed in the 2 lines examined (Kap-KL and Slc34a1-KL).…”
Section: Discussionmentioning
confidence: 99%
“…41 Soluble Klotho has been reported to act directly on the proximal tubules to increase phosphate excretion independent of Fgf23. 16 Moreover, Imai et al 42 reported that soluble Klotho suppresses Cyp27b1 through a pathway independent of cyclic adenosine monophosphate (cAMP) and protein kinase C (PKC). However, no measureable differences in serum soluble Klotho between knockout and wild-type mice were observed in the 2 lines examined (Kap-KL and Slc34a1-KL).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble Klotho acts as a humoral factor (72), potentially through an unknown cell-surface Klotho receptor, and as an enzyme (25, 202) regulating several cell surface glycoproteins. Indeed, secreted αKlotho inhibits insulin- and insulin-like growth factor I (IGF-I)-induced autophosphorylation of insulin and IGF-I receptor in vitro (99, 218).…”
Section: Fgf23 Functionmentioning
confidence: 99%
“…Blots were blocked in 5% nonfat milk in PBS for 1 h; incubated with rat monoclonal anti-Klotho (KM2076), anti-ICAM-1 (Cell Signaling), anti-VCAM-1 (R&D systems), anti-phospho eNOS (Cell signaling), or anti-phospho IjB (Cell Signaling) antibodies for over night; and incubated with peroxidase-conjugated secondary antibodies for 1 h. To monitor equal loading of proteins, membranes were incubated with anti-a-tubulin antibody (Calbiochem, La Jolla, CA). Immunoblots were developed with an ECL plus Western blotting detection system (GE Healthcare, Little Chalfont, Buckinghamshire, UK), as described previously [23,24].…”
Section: Western Blot Analysismentioning
confidence: 99%